Calcium channel blocker and risk of postoperation lymphatic-related complications among gynecologic malignances - Jiang, Haote; Sun, Mengxiao; Shao, Rongrong; Su, Shuyue; Zhang, Yuyang (Frontiers in Surgery, 2023)
Purpose This study was performed to assess the association of calcium channel blockers (CCB) and other potential factors with postoperative lymphatic-related morbidity in patients with cervical cancer and endometrial carcinoma. Methods Patients diagnosed with cervical cancer or endometrial carcinoma with pelvic lymphadenectomy between January 2017 and January 2022 were enrolled. Postoperative lymphatic-related morbidity was evaluated by calculating the lymph cyst occurrence within 3 months after surgery and the duration of pelvic drainage. Univariate analyses evaluating the risk factors for lymphatic-related morbidity were performed. Results Of a total of 251 patients, 52 patients were diagnosed with lymphatic cysts by B-ultrasound or computed tomography, and the duration of drainage from 110 patients exceeded the average number of days. Univariable analysis revealed that hypertension, CCB, and lymph node metastasis were independent predictors of postoperative complications. Conclusions This study demonstrated that CCB may be a factor associated with the incidence of postoperation lymph cysts, and CCB usage prolongs the duration of pelvic drainage.